David Delgado Ramos, Luis I. Gordillo Pérez (dir.), Cecilia Rosado Villaverde (coord.), La reforma del artículo 135 de la Constitución diez años después, Cizur Menor (Navarra), 2022, Thomson Reuters Aranzadi. - Arriola Echaniz, Naiara (Lex Social: Revista de Derechos Sociales, 2022)
-